Investigation on the Effect of Placement of Nitrogenous Fertilizer on the Yield of Wheat - Shrotriya, G C; Shekhawat, G S; Mathur, C M (Annals of Arid Zone, 2016)
A field trial to study the effect of nitrogen levels (33.6,50.4and 67 2 kg N/ha) 'and methods of fertilizer placement (broadcast. drilling 2 1/2" below seed and sideband placement) on wheat yield, was laidout at the Government Agricultural Farm, Sumerpur during rabi 1964-65 and 1965-66. It is inferred that application of 67.2 kgN/ha significantly increased the grain and straw yield over 33.6 and 50.4 kgN/ha levels. Drilling and sideband placement was as good as broadcast on sandy loam soils. Highest profit of Rs. 586.74was received with an application of 67.2 kgN/ha.